A framework for the current state of understanding of technology entrepreneurship - Abdullah, Syahida (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
Technology entrepreneurs and entrepreneurs may be similar in that they grab opportunities and optimize resources to attain high proft margins. Further, technology entrepreneurship is vital in the current globalization and liberalization economy. This paper presents a theoretical framework for understanding technology entrepreneurship through the lens of entrepreneurship and innovation. The proposed theoretical framework suggests a relationship between the entrepreneurial endeavors, which is the combined score of identifying and evaluating opportunity, developing business plan, optimizing resources, and managing the firm, with technology in the innovation realm. We believe that the proposed framework of technology entrepreneurship will add to the existing literature of entrepreneurship and understanding of technology entrepreneurs. This framework also has the potential to impact the teaching academia and administrators working in the area of entrepreneurship and technology entrepreneurship development; and entrepreneurs and technology entrepreneurs themselves.